2021
DOI: 10.33394/j-ps.v9i1.3816
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Climate Literacy Capacity of Level XI High School Students in Surabaya

Abstract: The climate problem today caused damage to infrastructures and many other living elements among mankind. As the prospected future leaders, students need to understand and to respond the effects of climate change. A person with climate literacy may enhance their ability and capacity to face climate challenges in the future. Climate literacy is the understanding of the influence of self and society on the climate. This research is conducted to give a general picture of climate literacy among high school students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Some studies show that students' climate literacy level needs improvement. Climate literacy analysis on aspects of competence of high school students in Surabaya shows that climate literacy in indicators identifies scientific phenomena as having a low category and a medium category for indicators explaining scientific phenomena and using scientific evidence (Nabilah & Hariyono, 2021). High school students' perceptions of climate change in Samboja, East Kalimantan, showed that most students did not fully understand climate change and only a third of the students in the study thought climate change was a global threat.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Some studies show that students' climate literacy level needs improvement. Climate literacy analysis on aspects of competence of high school students in Surabaya shows that climate literacy in indicators identifies scientific phenomena as having a low category and a medium category for indicators explaining scientific phenomena and using scientific evidence (Nabilah & Hariyono, 2021). High school students' perceptions of climate change in Samboja, East Kalimantan, showed that most students did not fully understand climate change and only a third of the students in the study thought climate change was a global threat.…”
Section: Introductionmentioning
confidence: 83%
“…Climate change has been one of the most pressing global challenges in recent years. Everything related to climate change is predicted to disrupt social systems and infrastructure, even ecosystems (Nabilah & Hariyono, 2021). One of the impacts of uncontrolled climate change can lead to natural disasters such as major floods caused by heavy rains (Nayan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indirectly, climate change involves nature's unique components: the at-mosphere, hydrosphere, and biosphere (Nayan et al, 2020). All aspects associated with climate change are anticipated to cause disruptions to social systems, infrastructure, and even ecosystems (Nabilah & Hariyono, 2021). Climate change also increases extreme events, such as harsh climate La Nina and El Nino, which can cause crop failure (Mardiyati et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Global phenomena with natural conditions that experience a shift or anomaly to the initial state (on average) over a long period (tens or hundreds of years) are the definition of climate change (Puspitasari & Surendra, 2016). Climate change is a natural event that is dangerous for humans because anything related to climate change can damage social structures, especially ecosystems (Nabilah & Hariyono, 2021). Some indicators of climate change that occur in Indonesia are air humidity, rainfall, air temperature, increased intensity of extreme weather such as rain accompanied by strong winds and storms, and others (Manik et al, 2017;Solihin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%